A Critical Analysis on the Book Technology of Knapped Stone - Mozhgan Jayez (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The only translated book into Persian about the classification of archaeological chipped stones is one of the most important technical books named Technology of Knapped Stone by M. Louise-Inizan and colleagues. This book, which is a great source in English and French, is introduced and criticized in this article. Since the book is the only one of its kind available in Persian, its value for the sake of educational purposes is unequivocal, but the quality of the print in translated version is highly questionable regarding the layout, images quality, and graphic design. Another aspect that is criticized in this article is the quality of translation which has been discussed regarding the Persian equivalents chosen for the words describing lithics and the ambiguity of technical descriptions. As a result, proper selection and uniformization of the Persian equivalents of technical vocabulary are recommended.